2021
DOI: 10.1080/14992027.2021.1881628
|View full text |Cite
|
Sign up to set email alerts
|

Key findings about hearing loss in the working-life: a scoping review from a well-being perspective

Abstract: Objective: This scoping review investigated key findings about hearing loss (HL) in the working life (WL) from a well-being perspective. Design: A scoping review protocol was used to search the literature and to explore and extract key findings. A narrative analysis of key findings was used to group the data into themes. Study sample: Fiftythree articles from 29 different journals were included in the analysis. Results: The narrative analysis identified three broad themes; individual aspects, work environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Participants also reported that, to a lesser extent, their HL negatively impacted their ability to work between the baseline and YR1 and YR2 follow-ups. This result aligns with a previous systematic review concluding that receiving CIs had a positive effect on the working life of individuals with HL in terms of better work performances related to, e.g., improved communication with colleagues and increased functioning [ 15 ]. From a health-economic perspective, it has been reported in a cost-benefit study that working-aged adults with profound HL have presented positive net benefits for CIs implanted at any age during working life [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Participants also reported that, to a lesser extent, their HL negatively impacted their ability to work between the baseline and YR1 and YR2 follow-ups. This result aligns with a previous systematic review concluding that receiving CIs had a positive effect on the working life of individuals with HL in terms of better work performances related to, e.g., improved communication with colleagues and increased functioning [ 15 ]. From a health-economic perspective, it has been reported in a cost-benefit study that working-aged adults with profound HL have presented positive net benefits for CIs implanted at any age during working life [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…These electrodes stimulate the auditory nerve, which transmits the impulses along the auditory pathway. Previous studies have reported that CIs can increase HRQoL in adults with severe to profound HL [ 12 , 13 , 14 ] and may improve employment status, employment satisfaction, career development, and work opportunities [ 15 ]. Individuals with CIs have also shown positive outcomes in work-related performance, e.g., overall increased functioning, fewer concerns about being marginalised in the workplace, and a decreased fear of losing their job after implantation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is a need for more research to determine the specifics of what promotes or hinders work-life well-being for people with HL. It is clear that a substantial part of research on HL and working life has focused solely on the negative consequences of HL in relation to employment and work and hearing-related challenges for employees with HL [16]. Consequently, the amount of research that investigate factors that promote a healthy working life for persons with HL is sparse.…”
Section: Hearing Loss In Working Lifementioning
confidence: 99%
“…Instruction is a more directive manner of psycho-education, whereas counselling is more person-centered. Recently, Granberg and Gustafsson (2021) concluded in a scoping review that the literature regarding rehabilitation services for employees with hearing loss is scarce. It is for example not well described which disciplines should be involved or which specific services should be provided.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the patients’ needs, the rehabilitation consists of interventions belonging to one or more of the four components mentioned above. Although it is increasingly acknowledged that it is important to address patient’s work needs in aural rehabilitation (Granberg and Gustafsson 2021 ; Zuriekat et al 2021 ), due to the lack of literature, it is unclear to what extent these kinds of services are currently provided and what the effects are of current services. To the best of our knowledge, a prospective evaluation of the NFR after the provision of any kind of aural rehabilitation has only been conducted in two recent studies (Gussenhoven et al 2017 ; van Leeuwen et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%